The Growth and Response Moulting of Mud Crabs (Scylla tranquebarica) Injected with Spinach Extract - Debi Rusadi; Putri, Dwi Septiani; Okto Rimandi Bakkara (Universitas Islam Lamongan, 2025)
Mud crab is a superior aquaculture commodity with a wide market potential both domestically and internationally. One of the main problems in mud crab cultivation is the long maintenance period and unequal moulting time. The purpose of this study was to determine the effect of spinach esxtract injection on the growth and response molting of mud crabs (Scylla tranquebarica). This reaserch was conducted in June-August 2024 for 60 days at the Sea Cages Maju Mandiri Group, Madong Village, Kampung Bugis Subdistrict, Tanjungpinang Kota District, Tanjungpinang City, Riau Islands Province. The method used in this study was an experimental method using a Completely Randomized Design (CRD) of 4 treatments and 3 replications. The results showed that the vitomolt injection treatment gave a significant difference (p>0.05) to the percentage of crab molting tested. The injection method of spinach extract (vitomolt) with a dose of 90 µg/g gave the highest molting percentage results of 83.33%, molting time at d-46, absolute weight growth of 89.00 g. Moulting stimulation with the spinach extract injection method (vitomolt) 90 μg/g can be applied to the cultivation of mud crabs (S. tranquebarica) because it can accelerate the molting process and growth of mud crabs.